HUBUNGAN ANTARA KONSEP DIRI DENGAN KESEJAHTERAAN PSIKOLOGIS PADA MAHASISWA UNIVERSITAS SAHID SURAKARTA (Lembaga Pengembangan Kinerja Dosen, 2023)
Self-concept is a mental picture or someone's perspective of what he has about himself. A person's self-concept can be formed through a learning process that starts from childhood to adulthood and influences from events or the environment that can have an impact on psychological well-being. This research was conducted with the aim of knowing the relationship between self-concept and psychological well-being of students at Sahid University of Surakarta. This research method uses quantitative methods with a total of 115 students who have certain criteria, which is being active students and coming from 9 undergraduate study programs at Sahid University, Surakarta. The sampling technique used in this study used a purposive sampling technique, with data analysis using product moment and simple linear regression. Based on the results of the correlations table, a correlation coefficient of 0.875 was obtained in the very strong category and a significance value of self-concept and psychological well-being of 0.000 <0.05 concluded that there was a relationship between self-concept and psychological well-being. Meanwhile, based on the results of the coefficient of determination (R square) of 0.765, which means that the effect of self-concept on psychological well-being is 76.5%. The results of the summary model show that Fcount = 368.238 with a significant level of 0.000 <0.05, it can be concluded that self-concept influences the psychological well-being of students at Sahid University, Surakarta. The higher the self-concept of a student, the higher his psychological well-being.